ANALISIS HUBUNGAN KINERJA PARTISIPASI DAN MANFAAT BAGI ANGGOTA KOPERASI (STUDI KASUS: KUD PUSPA MEKAR, KABUPATEN BANDUNG BARAT) - Emil Fatmala; Yanti Nuraeni Muflikh (Forum Agribisnis, 2013)
KUD Puspa Mekar is cooperation which has core business development specifically for dairy cow farm. Aim of this study wasto determine the general of KUD Puspa Mekar, identifying some factors which affected performance of cooperation, participation of members, and benefits for members also analyzing the relation among each factors toward performance of cooperation, participation of members, and benefits for members of KUD Puspa Mekar. Method of the research was Path Analysis, with these following exogen variables: vision (X1), capacity (X2), networking (X3), and resources (X4) of cooperation. Endogen variables which were measured such as performance of cooperation (Y1), participation of members (Y2), social (Y3) and economic (Y4) benefits. Factors affected the performance of cooperatives in order are vision, resources, participation, networking and capacity. Factors affected the participation of members was social benefits. The economic benefits less influance the participation of members. Performance of coopertives influance the social and economic benefits. KUD Puspa Mekar should keep more capital from internal rather than external. KUD Puspa Mekar should increase stimulus incentives to members through increase membership benefits. Increase the participation of members in terms of economic benefits can be enhanced by building the business unit in accordance with the expectations of members and build the business unit independently. KUD Puspa Mekar should improve and maintain the performance of cooperatives to social and economic benefits received by members will increase. Keyword(s): cooperation, performance, participation, benefit.